Synthesis and characterization of clay-biochars produced with facile low-temperature one-step in the presence of air for adsorbing methylene blue from aqueous solution - Liu, Rui; Li, Yuncong C.; Zhao, Zhimeng; Liu, Dandan; Ren, Jun; Luo, Yang (Frontiers in Environmental Science, 2023)
A facile and low-energy approach for biochar-supported clay preparation was developed at a low temperature (250℃) in the presence of air. A new type of engineered biochar by implanting clay particles on carbon surfaces had been successfully exploited as a low-priced adsorbent for environmental application. Two biomass feedstocks (tea and coffee wastes) were pretreated with kaolinite or montmorillonite suspension and then clay-biochars were synthesized using the facile one-step method. The adsorption performance, influencing factors, and mechanism of clay-biochars for methylene blue (MB) were investigated with adsorption experiments. The characterization results confirmed that clay exited on the biochar’s surface and the adsorption results revealed that biochar-supported clay had excellent MB adsorption capacities (>20 mg/g) at unadjusted solution pH and room temperature (25±1℃). Batch adsorption experiments showed that initial solution pH, ionic strength, and competing compounds affected MB adsorptions. The biochar-supported clay also had a potential of recycle and reusability for MB removal. The MB adsorption was predominately controlled by cation exchange (with both biochar and clay) and electrostatic interaction (with biochar only) mechanisms. This study provides a simple and environmental-friendly technology for creating high-efficiency clay-biochar adsorbent for removing cationic contaminants.